2018
DOI: 10.5350/sleep.hypn.2018.20.0160
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pilates Exercises on Motor Control of Inactive Middle-Aged Women

Abstract: Inactive lifestyle and its degrading consequences such as increased body fat mass, muscle atrophy and physical functioning problems are among factors affecting the motorcontrol in adulthood. Therefore, the aim of study was to investigate the effect of Pilates exercise on motor control indexes of inactive middle-aged women.Method: This was a semi experimental study with pretest and post test design performed on 43 inactive females with mean age of 44.4±5.1 yearswith low activity, body percent fat above 35%, WHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Studies have shown that regular physical activity can reduce abdominal fat intake, improve musculoskeletal control, reduce lower back pain, and improve the quality of balance and walking speed in the elderly (Irandoust et al, 2018(Irandoust et al, , 2019. Similarly, pilates exercise can decrease body fat mass and improve muscle atrophy, balance, and walking speed in inactive middle-aged women (Seghatoleslami et al, 2018). It was shown that skeletal muscle atrophy and skeletal muscle strength were significantly improved in elderly patients with sarcopenia after adequate vitamin D and amino acid treatment (Bauer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that regular physical activity can reduce abdominal fat intake, improve musculoskeletal control, reduce lower back pain, and improve the quality of balance and walking speed in the elderly (Irandoust et al, 2018(Irandoust et al, , 2019. Similarly, pilates exercise can decrease body fat mass and improve muscle atrophy, balance, and walking speed in inactive middle-aged women (Seghatoleslami et al, 2018). It was shown that skeletal muscle atrophy and skeletal muscle strength were significantly improved in elderly patients with sarcopenia after adequate vitamin D and amino acid treatment (Bauer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical activity can act on the clearance of body fat, improve musculoskeletal control, reduce low back pain, and improve the quality of balance and walking speed in the elderly (Irandoust, et al, 2019). Similarly, Pilates exercise can increase body fat mass and improve muscle atrophy, balance, and walking speed in middle-aged inactive women (Seghatoleslami, et al, 2018). Skeletal muscle atrophy and skeletal muscle strength have been shown to significantly improve in elderly patients with sarcopenia after adequate treatment with D and amino acids (Seeliger, et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 9 ] Accordingly, evidence indicates Pilates training increases strength, endurance, and flexibility, as well as improvement of physical conditions, psychological problems such as attention and concentration. [ 10 ] This type of training is not designed to reduce weight, but Pilates training can be considered a good option for people with overweight or obesity who have difficulty in adhering to those monotonous traditional physical exercises. [ 11 ] In addition to exercise, medical plants have been discovered and used in control and traditional treatment since prehistoric times.…”
Section: Introductionmentioning
confidence: 99%